Organizing Class Time and Covid-19: A reflection on pandemic/post-pandemic teaching - Peters, Brian (Apprendre et enseigner aujourd’hui, 2022)
Since 1997, I have been teaching in the Cegep system and at the university level. I have taught at four different institutions, five if one considers my teaching-assistant work as a graduate student. I have seen significant changes in student engagement and the classroom itself. The pandemic threw us all into a strange vortex where I had the chance to revamp my teaching, to modernize it, and to learn. In short, I learned how to restructure my courses and classroom time. My discoveries are captured here, in this personal essay.